Validity and Reliability of Turkish version of the Schizophrenia Hope Scale - Altun, Özlem Şahin; Özer, Duygu; Okanlı, Ayşe; Karakaş, Sibel Asi; Öztürk, Zeynep; Kayaoğlu, Kübra (My University, 2022)
This study aimed to evaluate the validity and reliability of the Turkish version of the Schizophrenia Hope Scale (SHS). This methodological study was carried out with 214 participants diagnosed with schizophrenia who were followed up in the psychiatry outpatient clinics of a university hospital between August 2021 and August 2022. Data were collected using an Information Form and the Schizophrenia Hope Scale (SHS). Language and content validity, exploratory and confirmatory factor analyses, item-total correlation, Cronbach alpha coefficient, and test-retest reliability methods were used in the validity and reliability analysis of the scale. As a result of the exploratory factor analysis, no item was excluded from the scale and it was determined that the scale has nine items and a single-factor structure. The single-factor structure of the scale was confirmed with the confirmatory factor analysis. The Cronbach Alpha coefficient of the scale was 0.901 and the factor loads ranged between 0.70 and 1.0. The test-retest correlation coefficient was r=0.959. The Turkish version of the scale was found to be valid and reliable. SCH is important since it represents the subjective meaning of hope from schizophrenic patients’ perspective and allows an easier measurement of the level of hope in this population. Mental health professionals can use SHS to determine or increase the level of hope of schizophrenia patients in their studies.
Keywords: Schizophrenia; reliability and validity; hope